Prenatal Alcohol Screening During Pregnancy by Midwives and Nurses. (11th June 2019) - Chiodo, Lisa M.; Cosmian, Caitlin; Pereira, Kristy; Kent, Nicole; Sokol, Robert J.; Hannigan, John H.
Abstract : Background: Alcohol use during pregnancy can have a variety of harmful consequences on the fetus. Lifelong effects include growth restriction, characteristic facial anomalies, and neurobehavioral dysfunction. This range of effects is known as fetal alcohol spectrum disorders (FASD). There is no amount, pattern, or timing of alcohol use during pregnancy proven safe for a developing embryo or fetus. Therefore, it is important to screen patients for alcohol use, inform them about alcohol's potential effects during pregnancy, encourage abstinence, and refer for intervention if necessary. However, how and how often nurses and midwives inquire about alcohol drinking during pregnancy or use recommended screening tools and barriers they perceive to alcohol screening has not been well established. Methods: This survey was sent to about 6, 000 American midwives, nurse practitioners, and nurses who provide prenatal care about their knowledge of the effects of prenatal alcohol exposure, the prevalence of alcohol use during pregnancy, and practices for screening patients' alcohol use. Participants were recruited by e‐mail from the entire membership roster of the American College of Nurse‐Midwives. Results: There were 578 valid surveys returned (about 9.6%). Analyses showed that 37.7% of the respondents believe drinking alcohol is safe during at least one trimester of pregnancy. Only 35.2% of respondents reported screening to assess patient alcohol use. Only 23.3% reported using a specific screening tool, and few of those were validated screens recommended for use in pregnant women. Respondents who believe alcohol is safe at some point in pregnancy were significantly less likely to screen their patients. Conclusions: Respondents who reported that pregnancy alcohol use is unsafe felt more prepared to educate and intervene with patients regarding alcohol use during pregnancy and FASD than respondents who reported drinking in pregnancy was safe. Perceived alcohol safety and perceived barriers to screening appeared to influence screening practices. Improving prenatal care provider knowledge about the effects of prenatal alcohol exposure and the availability of valid alcohol screening tools will improve detection of drinking during pregnancy, provide more opportunities for meaningful intervention, and ultimately reduce the incidence of FASD. Abstract : In a survey of 578 American nurse midwives, knowledge of the effects of prenatal alcohol exposure, prevalence of alcohol use during pregnancy, and screening practices were examined. 37.7% of respondents believe alcohol is safe during at least one trimester. Only 11.6% screened for drinking all the time; 35.2% reported screening some of the time. Perceived alcohol safety was related to screening practices. Improving nurse midwives' knowledge could improve detection of drinking during pregnancy and potentially reduce the incidence of FASD.